Primary Cesarean Section: A Gateway to Repeat Surgery : Primary Cesarean Section - Tabassum, Shagufta; Suman, Faiza; Tarin, Ayesha Uzaima; Rao, Saima Ayaz (Pakistan Journal of Health Sciences, 2025)
The rising rate of Cesarean Sections (CS) is a significant concern globally. While C-sections are lifesaving in many cases, an increasing number of unnecessary procedures pose risks to both mothers and babies. It has been found that the most common indication of CS is previous CS. Objective: To assess the indications and the factors leading to primary CS. Methods: The study was conducted at a tertiary care hospital of Pakistan employing non-probability consecutive sampling. A detailed history of participants revolving around their first CS was taken including indication and the associated demographics. All the information was entered on a specific proforma. Data analysis was conducted using SPSS software version 26.0. The primary outcome variable was the indication for primary cesarean section, while the secondary variables included factors contributing to the procedure. Results: A total of 264 women who had CS for at least one of their pregnancy were considered. The vast majority (n=195, 73.9%) were primigravida, had 4-6 antenatal visits (n=174, 65.9%) and underwent CS at term (180, 68.2%). There were more emergency CS (n=140.53%) performed at private clinics/hospitals (n=201. 57.4%). Regarding the indications of primary CS, the most prevalent was failed progress of labour, followed by oligohydramnios, breech presentation/transverse lie, fetal distress, reduced fetal movements and maternal request. Conclusion: It is need of time to scrutinize the indications of primary CS and to adopt potential strategies to minimize its number with the aim to lower overall CS rate.